Professional C++ - Gregoire, Marc; Solter, Nicholas A; Kleper, Scott J (John Wiley & Sons, Incorporated, 2011)
Essential reading for experienced developers who are determined to master the latest release of C++ Although C++ is often the language of choice from game programming to major commercial software applications, it is also one of the most difficult to master. With this no-nonsense book, you will learn to conquer the latest release of C++. The author deciphers little-known features of C++, shares detailed code examples that you can then plug into your own code, and reveals the significant changes to C++ that accompany the latest release. You'll discover how to design and build applications that solve real-world problems and then implement the solution using the full capabilities of the language. Appeals to experienced developers who are looking for a higher level of learning Drills down the extensive changes to the latest C++ standard, C++11, including enhancements made to run-time performance, standard library, language usability, and core languageZeroes in on explaining the more poorly understood elements of the C++ feature set and addresses common pitfalls to avoidIncludes case studies that feature extensive, working code that has been tested on Windows and Linux platformsIntertwines text with useful tips, tricks, and workarounds Packed with best practices for programming, testing, and debugging applications, this book is vital for taking your C++ skills to the next level.